Myocardial damage mechanisms in coronary artery bypass surgery (literature review) - Sh. Kh. Samadov; I. V. Koksheneva (Кардиоваскулярная терапия и профилактика)
The paper discusses modern views on myocardial damage mechanisms in coronary artery bypass surgery (CABG). The publications reviewed include those on molecular basis and pathophysiological pathways in ischemia/ reperfusion syndrome, as well as on potential cardioprotective strategies.